Emergency intubation of children outside of the operating room. Issue 3 (2nd January 2020) - Long, Elliot; Barrett, Michael J.; Peters, Cheryl; Sabato, Stefan; Lockie, Francis
Abstract: Intubation of children outside of the operating room is performed infrequently and is often associated with life‐threatening adverse events. This review aims to clarify the contributors to adverse events encountered during intubations outside of the operating room and provide preventative strategies. The primary contributors to adverse events during non‐operating room intubations are physiologically and situationally difficult airways; anatomically difficult airways are rare. Systems‐based changes, including a shared mental model, standardization in equipment and its location, checklist use, physiological resuscitation prior to resuscitation, dose titration of induction agent, multi‐disciplinary team training in the technical and nontechnical aspects of non‐operating room intubation, debrief post–real and simulated events, and regular audit of performance all reduce life‐threatening intubation‐related adverse events in children. Intubation of children outside of the operating room may be performed safely through engagement of all critical care specialties, shared learning, and focus on patient‐centered care delivery.